Pengaruh Media Sosial, Kepercayaan, dan Kualitas Produk Terhadap Keputusan Pembelian E-Commerce Blibli di Kota Batam - Sendy Claudia; Suhardi, Suhardi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to elaborate on the determinants of consumer purchasing decisions by emphasizing the role of social media, trust levels, and product quality in the Blibli e-commerce ecosystem in Batam City. The applied methodological framework is based on a descriptive quantitative approach involving 204 respondents with active transaction track records, selected through a purposive sampling technique based on the Jacob Cohen formula to ensure proportionality and validity of sample representation. Empirical data were collected through a structured questionnaire, then processed using comprehensive statistical analysis stages that include instrument validity and reliability testing, classical assumption evaluation, multiple linear regression modeling, and hypothesis testing through partial (t) and simultaneous (F) tests. The analysis results revealed that social media intensity contributed 14.1% to purchasing decisions, trust influenced 36.0%, while product quality influenced 40.4%. The coefficient of determination (R²) value of 86.4% indicates that the three exogenous variables simultaneously have substantial explanatory power towards variations in purchasing decisions. The t-test and F-test findings consistently confirm the significant influence of both individual and collective factors, thus confirming that strengthening digital presence, platform credibility, and consistent product quality are strategic foundations in guiding the preferences and purchasing intentions of Blibli consumers in Batam City.